O programa um computador por aluno na visão dos jovens das escolas públicas de Goiânia - Santos, Sebastião Pereira dos (2014)
The One Laptop per Child Program - PROUCA brings in its name an emphasis on the provision of equipment for the student. Unlike governmental initiatives prior to inclusion of computer equipment in the public schools, which were configured with the delivery of laboratories, this program has already stated in its name the intention to include the student with the delivery of a laptop. Thus, this study aimed at general check the forms as students of public schools covered in Goiânia with the PROUCA use the equipment received and the understanding that they have regarding the possibilities and limits of this program in their school reality. The PROUCA was established by Law no. 12,249, of June 14, 2010, with the proposal to promote digital inclusion and pedagogical development of the teaching and learning processes of students and teachers in the public schools in Brazil through the use of portable computers called educational laptops. With the aim of contributing to the development of systematic knowledge on this program, this research has focused on the uses that the young have of the laptops received from the program mentioned and the understanding of the limits and possibilities of them in their school reality. We attempted to investigate how the PROUCA was conceived and implemented in public schools. So, a literature review was made in order to verify the experiences already registered - in the dissertations of graduate programs in Brazilian universities, in some books already published and in the evaluation reports on the PROUCA, as well as an exploratory research through visits to some schools in the state of Goiás covered with equipment for this program. With the data obtained in this exploratory research, we defined the schools that would be locus of such research, as well as the methodological tools to guide it. It is a survey of qualitative nature, with a dialectical approach, checking the use that young people have of the equipment received from the PROUCA and the degree of digital inclusion provided by it. The theoretical framework adopted has mainly the theoretical contributions of Castells (2001; 2006), Levy (1993; 1997; 1999), Lemos (2002), Kellner and Share (2008), Buckingham (2007), Demo (1981; 2006; 2011), Belloni (2004; 2007; 2008), Franco (2007) and Gatti (2002; 2012). Using the focus group technique it was possible to hear the subjects of the research, in the case young students from two public schools in Goiânia, and analyze how they use the equipment received and how they manifest in its use in classroom activities. Besides the focus group technique, the research also relied on other methodological procedures, such as monitoring and observation of classes with the use of the equipment by students; semi-structured interviews with pedagogical coordinators, teachers and school managers and questionnaires. Among the results achieved with the investigation, it was possible to verify that the digital inclusion recommended by the program does not occur in the schools investigated, since it lacks the most elementary conditions for its operation in school reality.